Study of the Air‐Sea Momentum Flux of the Coastal Marine Boundary Layer During Typhoons. Issue 12 (17th June 2022) - Li, Qilong; Cheng, Xueling; Zeng, Xiaodong; Zhou, Guangqing; Huang, Jian; Wu, Lin; Zeng, Qingcun
Abstract: We analyzed the variations in the mean wind field, turbulence, and turbulent flux of three typhoons using observational data obtained from an offshore monitoring platform. The turbulent fluctuation intensity and friction velocity are found to increase with wind speed both before and after landfall with two different relationships as two distinct branches on the turbulence‐wind diagram. Turbulent fluctuation intensity is found to decrease with increasing wind speed during landfall because of the transition of land‐based turbulence to sea‐based turbulence. The relationships between the friction velocity and drag coefficient and the wind speed were similarly affected by whether the typhoon makes landfall, and the relative position of the landfall site of the typhoon to the observation site. Plain Language Summary: Winds blowing across the surface of the sea cause waves, which, in turn, affect the wind flow. This interaction has been well defined at low wind speeds, but has not previously been studied for strong winds such as typhoons. We found that this interaction is related to the location of landfall site within the typhoon, and it is different from the interaction at low wind speeds. By analyzing the turbulent data obtained from the costal platform in the track of typhoons, we found that the relationships between the turbulence fluctuation intensity, the friction velocities, the drag coefficients and wind speed at 10 m height are primarily determined by the wind direction such as onshore and offshore winds that are related to the landfall position of the typhoons. Key Points: We analyze four different landfall processes for typhoons The turbulent variables change differently with wind speeds during different typhoons period These changes are affected by the landfall site